Analysis of Digital Media and Learning Motivation as Determining Factors of Student Achievement - Reni Silviah (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Analysis of digital media and learning motivation as determining factors for student achievement is a scientific article with the aim of analyzing whether digital media and learning motivation influence student achievement. This research method uses a qualitative approach with a phenomenological method. The phenomenological approach is used to understand the meaning of individual life experiences related to a particular phenomenon in depth. The results of this article are: 1) Digital media is a determining factor for student achievement, 2) Learning motivation is a determining factor for student achievement. Apart from these two exogenous variables that influence the endogenous variable of student achievement, there are many other factors including the digital era, technology, and educational literacy.